2020
DOI: 10.3389/fpsyt.2020.460506
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of an Attachment-Related Stimulus on Oxytocin Reactivity in Poly-Drug Users Undergoing Maintenance Therapy Compared to Healthy Controls

Abstract: Background: Substance use disorders (SUDs) have been described as a dysfunctional way to compensate for deficiencies in that person's underlying attachment system. Furthermore, the neuropeptide oxytocin (OT), which is a critical component of the neurobiology of the attachment system, has been shown to effectively reduce addictive behavior and therefore has been discussed as a potential medication in SUD treatment. This study investigates variation in peripheral OT plasma levels as a function of exposure to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Although, in this study, no significant differences were observed between the different AR subgroups, mothers with an insecure AR tended to have stronger increases in oxytocin. Compared to healthy controls, males suffering from poly-drug-use disorder did not differ in oxytocin reactivity following AAP administration [ 32 ]. However, multi-drug users did not differ in AR from controls, making it rather difficult to directly compare these results with our study findings in AR subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although, in this study, no significant differences were observed between the different AR subgroups, mothers with an insecure AR tended to have stronger increases in oxytocin. Compared to healthy controls, males suffering from poly-drug-use disorder did not differ in oxytocin reactivity following AAP administration [ 32 ]. However, multi-drug users did not differ in AR from controls, making it rather difficult to directly compare these results with our study findings in AR subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigating oxytocin levels in the context of attachment in young and older men and women found that lower plasma oxytocin levels were associated with higher attachment anxiety in young men [ 38 ]. In contrast, higher baseline blood oxytocin levels were observed in poly-drug users compared to healthy controls [ 32 ]. From a methodological point of view, the comparability between oxytocin levels in saliva and blood and their reactivity in response to an external stimulus needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations